Tanshinone VI Inhibits the Expression of Intercellular Adhesion Molecule-1 and Vascular Cell Adhesion Molecule-1. (October 2013) - Nicolin, V.; Bossi, F.; Viggiano, A.; Valentini, R.; Nori, S.L.
This study investigated the possible antitumor mechanisms of action of Tanshinone VI, one of the components of Salvia miltiorrhiza Bunge, which is used in traditional Chinese herbal medicine. To this end, the expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1), were evaluated in-vitro in tumor necrosis factor-α (TNF-α)-stimulated endothelial cells, with, or without the addition of Tanshinone VI (10, 20, 30, or 40 mM) in the culture medium; the effects of Tanshinone VI on angiogenesis was also evaluated with an epithelial cell tube formation assay and its toxicity was evaluated with a colorimetric (MTT) cell viability assay. The results showed that the up-regulation of ICAM-1 and VCAM-1 induced by TNF-α was dose-dependently inhibited by Tanshinone VI, with restoration of control levels at the dose of 40 mM; Tanshinone VI also had a remarkable anti-angiogenesis effect, already at the dose of 10 mM, while none of the doses tested had significant effects on cell viability. These results indicate that the antitumor properties of Tanshinone VI can be ascribed to the inhibition of cell adhesion, due to blockage of the up-regulation of cell adhesion molecules, with the consequent inhibition of metastases formation and/or angiogenesis. The lack of toxic effects at the dosage used makes Tanshinone VI a good candidate for its therapeutic use in humans.